2018
DOI: 10.3390/molecules23092116
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Discovery and Synthesis of Potential Transketolase Inhibitors

Abstract: Transketolase (TKL) plays a key role in plant photosynthesis and has been predicted to be a potent herbicide target. Homology modeling and molecular dynamics simulation were used to construct a target protein model. A target-based virtual screening was developed to discover novel potential transketolase inhibitors. Based on the receptor transketolase 1 and a target-based virtual screening combined with structural similarity, six new compounds were selected from the ZINC database. Among the structural leads, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…Understanding the S. turcica germination process and appressorium development, as well as related biological events, could lead to improved disease control, as these processes are one of the earliest stages of fungal preparation for plant infection. Our laboratory has a long‐time interest in and focuses on the molecular control of S. turcica pathogenicity and fungicide development (Cao et al, 2020 ; Huo et al, 2018 ). Fieldwork observations suggest that inhibition of appressorium development is an efficient strategy against S. turcica ‐mediated maize foliar disease (Zeng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the S. turcica germination process and appressorium development, as well as related biological events, could lead to improved disease control, as these processes are one of the earliest stages of fungal preparation for plant infection. Our laboratory has a long‐time interest in and focuses on the molecular control of S. turcica pathogenicity and fungicide development (Cao et al, 2020 ; Huo et al, 2018 ). Fieldwork observations suggest that inhibition of appressorium development is an efficient strategy against S. turcica ‐mediated maize foliar disease (Zeng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The herbicidal activities of the test compounds against B. campestris , A. retroflexus and D. sanguinalis were evaluated by the small cup method and foliar spray method at 200 mg/L, according the following procedure [33,34]. With respect to the small cup method, generally, the test compound (20 mg) was dissolved in N , N -dimethylformamide (DMF) (1 mL) and then diluted in water containing 0.1% Tween 80 to a final concentration of 200 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, several approaches are available in the search and development of drugs [ 90 , 91 , 92 , 93 ]. Planning based on structure and mechanism of action has proven to be an efficient and less expensive strategy for developing new drugs [ 94 ]. A critical study showed that the most common drug targets are enzymes, particularly oxidoreductases, transferases and lyases.…”
Section: Search For New Therapeutic Options—a Journeymentioning
confidence: 99%
“…Virtual screening allows a search for several chemical libraries of small molecules and selects those that best interact with the specific target’s catalytic site [ 94 , 143 , 144 , 145 ]. The application of this technique is well accepted, mainly in the lead discovery phase [ 146 , 147 ].…”
Section: Search For New Therapeutic Options—a Journeymentioning
confidence: 99%